2016
DOI: 10.1111/nyas.12977
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes: what are they and what do they do?

Abstract: Electronic cigarettes (ECIGs) use electricity to power a heating element that aerosolizes a liquid that often contains solvents, flavorants, and the dependence-producing drug nicotine for user inhalation. ECIGs have evolved rapidly in the past 8 years, and the changes in product design and liquid constituents affect the resulting toxicant yield in the aerosol and delivery to the user. This rapid evolution has been accompanied by dramatic increases in ECIG use prevalence in many countries, including among adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
284
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(289 citation statements)
references
References 282 publications
(702 reference statements)
2
284
0
3
Order By: Relevance
“…Sleiman et al (2016) identified two other potential carcinogens in EC vapour: propylene oxide and glycidol. Other articles showed similar results, with increasing levels of toxicants when higher-powered devices were used (Laugesen 2008;McAuley et al 2012;Goniewicz et al 2014b;Hutzler et al 2014;Kosmider et al 2014;Tayyarah and Long 2014;Geiss et al 2015;Herrington and Myers 2015; Zucchet and Schmaltz 'Connell et al 2015;El-Hellani et al 2016;Jo and Kim 2016;Leigh et al 2016;Sleiman et al 2016;Talih et al 2016). The amount and types of these degradation products vary substantially in different studies, making generalizations about the health effects of ECs difficult.…”
Section: Composition Of Unflavoured Ec Aerosolsmentioning
confidence: 54%
See 3 more Smart Citations
“…Sleiman et al (2016) identified two other potential carcinogens in EC vapour: propylene oxide and glycidol. Other articles showed similar results, with increasing levels of toxicants when higher-powered devices were used (Laugesen 2008;McAuley et al 2012;Goniewicz et al 2014b;Hutzler et al 2014;Kosmider et al 2014;Tayyarah and Long 2014;Geiss et al 2015;Herrington and Myers 2015; Zucchet and Schmaltz 'Connell et al 2015;El-Hellani et al 2016;Jo and Kim 2016;Leigh et al 2016;Sleiman et al 2016;Talih et al 2016). The amount and types of these degradation products vary substantially in different studies, making generalizations about the health effects of ECs difficult.…”
Section: Composition Of Unflavoured Ec Aerosolsmentioning
confidence: 54%
“…The high level of formaldehyde is especially concerning as this compound is a potent carcinogen and is toxic to the human reproductive system (Duong et al 2011). Formaldehyde and other carbonyls are also problematic because their concentrations can be high and correlated with the power of the device (El-Hellani et al 2016). This is of special concern with newer generation high-powered devices.…”
Section: Composition Of Unflavoured Ec Aerosolsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are frequently marketed as having a role in smoking cessation. ENDS liquids contain nicotine, at least one solvent agent (usually propylene glycol and/or glycerin) as well as flavours [1]; however, they can contain any variety of compounds and may contain no nicotine. The make-up of the liquid, the power output of the device and the strength of user inhalation influence the yield of substance inhaled from a given ENDS aerosol [1].…”
Section: Introductionmentioning
confidence: 99%